Avatars: the wonderful and the weird at Second Life - Gomes, Laura Graziela (2019)
The article aims to discuss the wonderful and the strange in the Second Life virtual world, as well as the engagement and care relationships that human users bestow on their creatures, the avatars. Since 2007, I have been dedicating myself to observe and follow the development of this world and its possible ways of life in different aspects, as well as the logical, symbolic and subjective premises on which all existence develops and sustains, especially the economy of this virtual world, making Second Life one of the oldest and most successful digital platforms in operation